SPECIFICS OF METABOLIC SYNDROME PATHOPHYSIOLOGY IN WOMEN AT DIFFERENT PHASES OF CLIMACTERIC PERIOD - V. B. Mychka; S. N. Tolstov; I. A. Salov (Российский кардиологический журнал)
Aim. To study the specifics of metabolic syndrome (MS) course in women at different stages of climacterics and relationship with body mass and adipose tissue localization pattern.Material and methods. Totally 138 women included during the climacteric period: 1 st group — 52 women in premenopausal period; 2nd group — 86 women in early postmenopause. The age of participants for the 1st group was 49,1 (48,0;51,0) years, 2nd group — 53,9 (50,0;56,0) years. We studied lipid profile, MK and carbohydrate metabolism including C-peptide, IRI and HOMA-IR. The method for the hard phase IEA in blood plasma used to measure SHBG and dihydroepiandrosterin-sulphate (DHEAS). ABPM was performed for 24 hours by oscillometric method.Results. Most women in postmenopausal period had adverse metabolic changes in lipid and carbohydrate metabolisms relevant for MS. Lipid profile disorders in women at menopausal switch were found with the highest levels during early postmenopause. The highest intergroup differences were found by the levels of TG of the blood and relationship of TG to HDL, non-HDL. Also the increase of HOMA-IR marked in women at postmenopause 1,49 (0,80-2,2) and 0,82(0,3-1,4) units, resp., p<0,05).Two types of MS selected — MetONM and MS with overweight with the prevalence of the second type MS in 90,6% of women. The specifics of clinical presentation of MS in overweight is the severity of metabolic and hormonal changes — high levels of TG (2,2±1,7 и 1,65±0,3 mmol/L, p<0,01) and MK (371 ±84,4 и 342±71,8 mcmol/L, p<0,05), HOMA-IR (3,9 (1,8;6,0) и 2,8 (1,7;4,5) units, p<0,05), resp., and decrease of SHBG (387,7 (319,7;517,0) и 623,8 (396,3;720,0) nmol/L, p<0,01); more severe course of AH noted.